Anxiety in the Orthopaedic Patient: Using PROMIS to Assess Mental Health - Beleckas, Casey M. (Qual Life Res, 2018)
PURPOSE: This study explored the performance of the Patient Reported Outcomes Measurement Information System (PROMIS) Anxiety assessment relative to the Depression assessment in orthopedic patients, the relationship between Anxiety with self-reported Physical Function and Pain Interference, and to determine if Anxiety levels varied according to the location of orthopedic conditions. METHODS: This cross-sectional evaluation analyzed 14,962 consecutive adult new-patient visits to a tertiary orthopedic practice between 4/1/2016 and 12/31/2016. All patients completed PROMIS Anxiety, Depression, Physical Function, and Pain Interference computer adaptive tests (CATs) as routine clinical intake. Patients were grouped by the orthopedic service providing care and categorized as either affected with Anxiety if scoring >62 based on linkage to the Generalized Anxiety Disorder-7 survey. Spearman correlations between the PROMIS scores were calculated. Bivariate statistics assessed differences in Anxiety and Depression scores between patients of different orthopedic services. RESULTS: Twenty percent of patients scored above the threshold to be considered affected by Anxiety. PROMIS Anxiety scores demonstrated a stronger correlation than Depression scores with Physical Function and Pain Interference scores. Patients with spine conditions reported the highest median Anxiety scores and were more likely to exceed the Anxiety threshold than patients presenting to sports or upper extremity surgeons. CONCLUSIONS: One in 5 new orthopedic patients reports Anxiety levels that may warrant intervention. This rate is heightened in patients needing spine care. Patient-reported Physical Function more strongly correlates with PROMIS Anxiety than Depression suggesting that the Anxiety CAT is a valuable addition to assess mental health among orthopedic patients.